Unveiling the aesthetic connection: Balinese wayang characters and the 'prodigal son' bible story - Andreas James Darmawan; I Nyoman Sedana; Martinus Dwi Marianto (Pascasarjana Institut Seni Indonesia Surakarta, 2023)
The Prodigal Son, a well-known biblical parable cherished by children, has never been depicted using Balinese wayang, presenting an opportunity for cultural enrichment. This research aims to select appropriate Balinese wayang characters for the Bible story